2002
DOI: 10.1577/1548-8659(2002)131<1203:eotopc>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Turbidity on Prey Consumption by Prairie Stream Fishes

Abstract: Reduced suspended‐sediment loads (i.e., turbidity) in many Midwestern prairie rivers have been hypothesized as contributing to the replacement of species that historically occupied highly turbid main‐channel habitats by visually feeding species that are competitively superior in less‐turbid waters. We examined the relationship between prey consumption and turbidity for six fish species from the Canadian River (New Mexico, Oklahoma, and Texas) and found experimental support for this hypothesis. Among species ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 16 publications
(2 reference statements)
1
55
1
Order By: Relevance
“…Changes in stream flow probably are not the only stressor affecting the regional fauna. Decreases in turbidity, to which native species are adapted (Bonner and Wilde 2002), probably have facilitated the replacement of native species by sight-feeding invasive species in regional rivers (Cross and Moss 1987). This decline in turbidity below impoundments can increase predation risk for many minnow species (Rahel and Thel 2004).…”
Section: ]mentioning
confidence: 99%
“…Changes in stream flow probably are not the only stressor affecting the regional fauna. Decreases in turbidity, to which native species are adapted (Bonner and Wilde 2002), probably have facilitated the replacement of native species by sight-feeding invasive species in regional rivers (Cross and Moss 1987). This decline in turbidity below impoundments can increase predation risk for many minnow species (Rahel and Thel 2004).…”
Section: ]mentioning
confidence: 99%
“…Moderation of turbidity may be giving the sand shiner a competitive advantage over other native fish species. Bonner and Wilde (2002) found that prey consumption by sand shiners was greatest at moderate turbidity levels, which could explain the success of sand shiner within the Bighorn River study area.…”
Section: Discussionmentioning
confidence: 92%
“…(Mueller and Pyron, 2011). Conditions downstream of reservoirs may provide other benefits to sand shiners, such as decreased turbidity, which has been shown to negatively impact feeding on terrestrial and aquatic insects by this species (Bonner and Wilde, 2002). Suckermouth minnows and slenderhead darters prefer fast flowing waters and require high-velocity areas during spring for spawning (Brewer and others, 2006).…”
Section: Effects Of Flow Alteration On Fish Assemblagesmentioning
confidence: 99%
“…Several studies have shown changes in fish assemblage structure associated with water resource development and reservoir operations (Bain and others, 1988;Bonner and Wilde, 2002;Marchetti and Moyle, 2001;Perkin and Bonner, 2011). Our analysis examines a temporal sequence of fish assemblage structure in response to reservoir construction in two different stream systems representing different ecological settings.…”
Section: Effects Of Flow Alteration On Fish Assemblagesmentioning
confidence: 99%